Range Measurement and a Habitat Suitability Map for the Norway Rat in a Highly Developed Urban Environment - Dauda Taofik Oyedele,; Shahrul Anuar Mohd Sah,; Liyana Kairuddin,; Wan Mohd Muhiyuddin Wan Ibrahim, (Tropical Life Sciences Research, 2015)
Studies of habitat suitability (HS) are essential when animals’ habitats have been altered or when animals migrate to a habitat different from their natural habitat. This study assessed HS and used an integrated geographic information system in the assessment of Rattus norvegicus in a highly developed urban environment. Using data from the Campbell market and the police quarters of George Town, Malaysia, home range (through the use of 100% Minimum Convex Polygon [MCP], 95% MCP and 95% Harmonic Mean [HM]) was estimated. Home range for male rats at Campbell market reached an asymptote, with a slight increase, at 96 radio fixes (home range = 133.52 m2; core area = 29.39 m2). Female rats reached an asymptote at 62 radio fixes (home range = 13.38 m2; core area = 9.17 m2). At Campbell market, male rats emerged at 1900 hours every day, whereas females emerged at 2000 hours; at police quarters, the most common time of emergence for males was 2000 hours and for females was 2200. Raster charts of R. norvegicus showed that rat hot spots can be grouped into 4 zones (market, shop houses, settlement and general places). The standardised raster chart isolated the market as the major rallying points of the rats (hot spots) by producing the highest rats frequencies of 255. All of the habitat suitability thresholds, including the built-up points, skip bins, water source and nature of the site explored in this study, produced a structural pattern (monotonic increase or decrease) of habitat suitability. Kajian kesesuaian habitat (KS) sangat diperlukan apabila habitat haiwan telah diubahsuai atau haiwan berhijrah ke habitat yang sangat berbeza daripada habitat asli mereka. Kajian ini dijalankan untuk menaksir KS dan mengabungkan sistem maklumat geografi untuk Rattus norvegicus di kawasan perbandaran yang sangat membangun. Menggunakan data daripada pasar Campbell dan kuarters polis di George Town, Malaysia, kawasan rayau (kaedah 100% Minimum Convex Polygon [MCP], 95% MCP dan 95% Harmonic Mean [HM]) dianggarkan. Kawasan rayau tikus jantan di pasar Campbell mencapai asimptot pada 96 isyarat radio dengan sedikit peningkatan (kawasan rayau = 133.52 m2; titik pusat = 29.39 m2). Tikus betina mencapai asimptot pada 62 isyarat radio (kawasan rayau = 13.38 m2; titik pusat = 9.17 m2). Di pasar Campbell, tikus jantan muncul pada jam 1900 setiap hari manakala betina muncul pada jam 2000 tetapi di kuarters polis, masa kebiasaan kemunculan untuk jantan adalah pada jam 2000 dan betina pada jam 2200. Carta raster R. norvegicus menunjukkan titik tumpuan tikus boleh dikategorikan kepada 4 zon (pasar, rumah kedai, kediaman dan kawasan tumpuan awam). Carta raster yang diseragamkan memisahkan kawasan utama titik tumpuan tikus ialah di pasar dengan frekuensi tikus tertinggi iaitu 225. Semua analisis kesesuaian habitat termasuk kawasan dibangunkan, kawasan tong sampah, sumber air dan tapak semulajadi dalam kajian ini mempamerkan corak berstruktur (peningkatan atau penurunan monotonik) kesesuaian habitat.